Pengaruh Return on Equity, Leverage, Collateralizable Asset dan Asset Growth terhadap Kebijakan Dividen dengan Kepemilikan Manajerial sebagai Variabel Moderasi - Hilda Yani; Bambang Satriawan; Robin (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to analyze the influence of Return on Equity (ROE), Leverage (DER), Collateralizable Asset (CA), and Asset Growth (AG) on dividend policy, with managerial ownership as a moderating variable. Dividend policy is one of the key decisions made by corporate management to enhance shareholder welfare. This research focuses on manufacturing companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange (IDX) from 2018 to 2022. A quantitative method was employed, utilizing secondary data obtained from www.idx.co.id. After applying sampling techniques, 19 companies were selected as the research sample from a population of 30 companies. The results of the study indicate that Return on Equity (ROE), Leverage (DER), and Asset Growth (AG) do not have a significant influence on dividend policy, whereas Collateralizable Asset (CA) shows a significant influence. Additionally, managerial ownership does not moderate the relationships between Return on Equity, Leverage, Collateralizable Asset, or Asset Growth and dividend policy. These findings suggest that internal company factors such as profitability, capital structure, and asset growth, along with managerial ownership, are not always determinants of dividend policy decisions in manufacturing companies in the food and beverage sub-sector.